North Caucasus Regional Branch of All-Union Society of Old Bolsheviks (1930–1935) - A. A. Aganov; O. A. Eldinov (Научный диалог, 2025)
This article examines the activities of the North Caucasus Regional Branch of the All-Union Society of Old Bolsheviks during the early 1930s. Utilizing unpublished administrative materials from the Center for Documentation of Recent History in the Rostov Region as its primary source base, the study identifies the main areas of focus for the North Caucasus branch. The history of the Society is traced from its establishment to its dissolution (January 1922 – May 1935). The findings suggest that the regional branch was in a state of crisis even before the assassination of prominent Soviet party and state leader S. M. Kirov, which triggered a search for “enemies of the people” within the USSR, including among the ranks of the old Bolsheviks. Notably, it is reported that shortly before Kirov's death, the organization's leadership made a significant political misstep when one of its members, I. D. Chentsov, invited opposition figures to celebrate the 15th anniversary of Rostov-on-Don's liberation by Red Army forces from White Guards. Chentsov was subsequently expelled from the organization on political grounds and later repressed. The study establishes that the decline of the regional branch coincided with this critical error. Furthermore, it is noted that in May 1935, following directives from party leadership, the All-Union Society of Old Bolsheviks and all its regional branches self-dissolved.